2019
DOI: 10.1155/2019/6263249
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Risk Assessment of Lymph Node Metastasis in cT1 Lung Cancer: A Retrospective Study from Eastern China

Abstract: Background Lymph node status of clinical T1 (diameter ≤ 3 cm) lung cancer largely affects the treatment strategies in the clinic. In order to assess lymph node status before operation, we aim to develop a noninvasive predictive model using preoperative clinical information. Methods We retrospectively reviewed 924 patients (development group) and 380 patients (validation group) of clinical T1 lung cancer. Univariate analysis followed by polytomous logistic regression was performed to estimate different risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Notably, some LUAD patients develop lymph node metastasis when the diameter of the primary tumor remains very small. Early lymph node metastasis significantly affects the long-term survival of patients ( Liu et al, 2019 ; Zhang et al, 2019a ), and our study verified that stage-T1 patients with lymph node metastasis have a shorter OS. ( Takada et al, 2020 ) demonstrated that early lymph node metastasis in breast cancer is related to tumor-infiltrating lymphocytes, whereas no relevant research has been published on early lymph node metastasis of lung cancer.…”
Section: Discussionsupporting
confidence: 73%
“…Notably, some LUAD patients develop lymph node metastasis when the diameter of the primary tumor remains very small. Early lymph node metastasis significantly affects the long-term survival of patients ( Liu et al, 2019 ; Zhang et al, 2019a ), and our study verified that stage-T1 patients with lymph node metastasis have a shorter OS. ( Takada et al, 2020 ) demonstrated that early lymph node metastasis in breast cancer is related to tumor-infiltrating lymphocytes, whereas no relevant research has been published on early lymph node metastasis of lung cancer.…”
Section: Discussionsupporting
confidence: 73%
“…We focused on these markers as they are routinely tested in standard clinical practice within the preoperative assessment and therefore immediately available essentially in all centers performing lung resections for cancer. Other serum markers such as Carcino-Embryonic Antigen (CEA)-which has also been associated with occult nodal spread in early stage NSCLC [1,10,11]-are not typically measured before surgical treatment of early NSLCL in many centers. Recently published literature on this topic also corroborated the basic idea of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that imaging invasiveness, lesion diameter, and depth were predictive factors for lymph node metastasis in T1 lung adenocarcinoma. Additionally, the micropapillary subtype, as determined by pathological analysis, was identified as a risk factor specifically for N2 skip lymph node metastasis 10–12 . Previous studies have examined the risk factors for lymph node metastasis in T1 lung cancer, often focusing on either N1 or N2 endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the micropapillary subtype, as determined by pathological analysis, was identified as a risk factor specifically for N2 skip lymph node metastasis. 10 , 11 , 12 Previous studies have examined the risk factors for lymph node metastasis in T1 lung cancer, often focusing on either N1 or N2 endpoints. However, in clinical practice, the risk factors for N1 and N2 metastasis can differ.…”
Section: Discussionmentioning
confidence: 99%